2014
DOI: 10.1109/tie.2013.2288231
|View full text |Cite
|
Sign up to set email alerts
|

Variable-Gear EV Reluctance Synchronous Motor Drives—An Evaluation of Rotor Structures for Position-Sensorless Control

Abstract: The reluctance synchronous motor (RSM) is identified to be well suited for the variable-gear (VG) electric vehicle (EV) drive. It is shown in this paper, however, that the RSM drive's position-sensorless capability is limited at zero or very small current magnitudes due to a limited saliency magnitude. In this paper, a novel epoxy-resin-casted rotor with no iron ribs is proposed to increase the saliency of the RSM at zero reference current. This rotor RSM is simulated in finite-element (FE) analysis, built, ev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 27 publications
(56 reference statements)
0
10
0
Order By: Relevance
“…(25) and (27), the maximal torque is obtained when I 3 = I 5 . Moreover, the locus of the current fundamental and harmonics required to achieve a maximal torque per ampere is shown on Fig.…”
Section: Theoretical Aspectmentioning
confidence: 94%
See 1 more Smart Citation
“…(25) and (27), the maximal torque is obtained when I 3 = I 5 . Moreover, the locus of the current fundamental and harmonics required to achieve a maximal torque per ampere is shown on Fig.…”
Section: Theoretical Aspectmentioning
confidence: 94%
“…Therefore, a renewed interest in reluctance machines has emerged, and in particular in the Synchronous Reluctance Machine (SynRM) from a design point of view as in [5,7,10,11,14,15] and a control point of view as in [27,29,32]. It has been reported that the SynRM delivers competitive results in comparison with the Induction Machine (IM) in [12].…”
Section: Introductionmentioning
confidence: 99%
“…Current is represented as a circle, the voltage required at a particular torque, at any speed, is represented as an ellipse, while the torque is a hyperbola. Utilising (4), (5), tan δ = i qn /i dn , the expression for normalised voltage v n in terms of T n , ω n and δ is given by…”
Section: Mathematical Evaluation Of the Voltage Dip Margin Of A Synrmmentioning
confidence: 99%
“…As this choice is very critical for the mechanical strength of the rotor core at high speed, it has been decided to fill the flux barriers with epoxy adhesive resin. This technological solution allows to improve the electro-mechanical performance of the machine and to minimize the cross-magnetization effects, thus improving the robustness of a possible sensorless control [7]- [8]. The use of the resin inside the barriers has required an accurate mechanical analysis to verify if the rotor structure was able to withstand the mechanical stress at high speed.…”
Section: Introductionmentioning
confidence: 99%